Analysis of Favipiravir Adverse Drug Reactions during COVID-19 Pandemic: A Retrospective Study Based on Iraqi Pharmacovigilance Center Database - Yasir Ezalden Noori Alkashab; Inam S. Arif; Manal M. Younus; Mohammed M. Mohammed; Abdullah M. Alrawi; Salim Hamadi (College of Pharmacy / Mustansiriyah University, 2024)
The "severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)" was the reason behind the recent pandemic "COVID-19" that started from Wuhan, china, and rapidly spread to many regions of the world. Research in Drug repurposing processes to treat this novel coronavirus involved many medications, one of the most discussed is Favipiravir. The objective of the current work was aimed towards Examining the cause, severity, preventability, predictability, and outcome of favipiravir-associated adverse events that had been reported in Iraq. In terms of adverse drug responses, "Gastrointestinal disorders" accounted for the majority (57.4%), followed by "Cardiac disorders" (35.2%), and "Investigations" (abnormal lab test results) (13%). The causality of these reactions Is majorly "Possible" (62%). Severity level 1 (40.9%) and 2 (41.8%). Ninety-nine percent of the ADRs are expected. The majority of the ADRs are non-Preventable (76.3%). The main outcome is Recovered / Resolved (44.5%). About (50%) of the ADRs were serious.